rDromaserpin: A Novel Anti-Hemostatic Serpin, from the Salivary Glands of the Hard Tick Hyalomma dromedarii - Aounallah, Hajer; Fessel, Melissa Regina; Goldfeder, Mauricio Barbugiani; Carvalho, Eneas; Bensaoud, Chaima; Chudzinski-Tavassi, Ana Marisa; Bouattour, Ali; M'ghirbi, Youmna; Faria, Fernanda (Toxins, 2021)
Hemostatic disorders are caused either by platelet-related dysfunctions, defective blood coagulation, or by a combination of both, leading to an increased susceptibility to cardiovascular diseases (CVD) and other related illnesses. The unique specificity of anticoagulants from hematophagous arthropods, such as ticks, suggests that tick saliva holds great promise for discovering new treatments for these life-threatening diseases. In this study, we combined in silico and in vitro analyses to characterize the first recombinant serpin, herein called Dromaserpin, from the sialotranscriptome of the Hyalomma dromedarii tick. Our in silico data described Dromaserpin as a secreted protein of ~43 kDa with high similarities to previously characterized inhibitory serpins. The recombinant protein (rDromaserpin) was obtained as a well-structured monomer, which was tested using global blood coagulation and platelet aggregation assays. With this approach, we confirmed rDromaserpin anticoagulant activity as it significantly delayed plasma clotting in activated partial thromboplastin time and thrombin time assays. The profiling of proteolytic activity shows its capacity to inhibit thrombin in the micromolar range (0.2 to 1 μM) and in the presence of heparin this inhibition was clearly increased. It was also able to inhibit Kallikrein, FXIa and slightly FXIIa, with no significant effect on other factors. In addition, the rDromaserpin inhibited thrombin-induced platelet aggregation. Taken together, our data suggest that rDromaserpin deserves to be further investigated as a potential candidate for developing therapeutic compounds targeting disorders related to blood clotting and/or platelet aggregation.
Keywords: Serpins; thrombin inhibitor; sekvence aminokyselin; Models, Molecular; salivary glands; Computer Simulation; počítačová simulace; serpin; Protein Conformation; antikoagulancia; molekulární modely; zvířata; Anticoagulants; Ixodidae; Amino Acid Sequence; fylogeneze; anticoagulants; Blood Coagulation; Hyalomma dromedarii; serpiny; Phylogeny; hemokoagulace; konformace proteinů; Animals